Pelleted Bone Marrow Derived Mesenchymal Stem Cells Are Better Protected from the Deleterious Effects of Arthroscopic Heat Shock - Kalamegam, Gauthaman; Abbas, Mohammed; Gari, Mamdooh; Alsehli, Haneen; Kadam, Roaa; Alkaff, Mohammed; Chaudhary, Adeel; Al-Qahtani, Mohammed; Abuzenadah, Adel; Kafienah, Wael; Mobasheri, Ali (Frontiers in Physiology, 2016)
Introduction: The impact of arthroscopic temperature on joint tissues is poorly understood and it is not known how mesenchymal stem cells (MSCs) respond to the effects of heat generated by the device during the process of arthroscopy assisted experimental cell-based therapy. In the present study, we isolated and phenotypically characterized human bone marrow mesenchymal stem cells (hBMMSCs) from osteoarthritis (OA) patients, and evaluated the effect of arthroscopic heat on cell viability in suspension and pellet cultures. Methods: Primary cultures of hBMMSCs were isolated from bone marrow aspirates of OA patients and cultured using DMEM supplemented with 10% FBS and characterized for their stemness. hBMMSCs (1 x 106 cells) cultured as single cell suspensions or cell pellets were exposed to an illuminated arthroscope for 10, 20 or 30 min. This was followed by analysis of cellular proliferation and heat shock related gene expression. Results: hBMMSCs were viable and exhibited population doubling, short spindle morphology, MSC related CD surface markers expression and tri-lineage differentiation into adipocytes, chondrocytes and osteoblasts. Chondrogenic and osteogenic differentiation increased collagen production and alkaline phosphatase activity. Exposure of hBMMSCs to an illuminated arthroscope for 10, 20 or 30 min for 72 h decreased cell proliferation in cell suspensions (63.27% at 30 min) and increased cell proliferation in cell pellets (62.86% at 10 min and 68.57% at 20 min). hBMMSCs exposed to 37C, 45C and 55C for 120 seconds demonstrated significant upregulation of BAX, P53, Cyclin A2, Cyclin E1, TNF-α, and HSP70 in cell suspensions compared to cell pellets. Conclusions: hBMMSC cell pellets are better protected from temperature alterations compared to cell suspensions. Transplantation of hBMMSCs as pellets rather than as cell suspensions to the cartilage defect site would therefore support their viability and may aid enhanced cartilage regeneration.